Avaliação da atividade leishmanicida do óleo essencial de Vanillosmopsis arborea (Asteracea) Baker no tratamento da leishmaniose tegumentar murina - Esposito, Wilany Chagas Cardoso (2015)
Leishmaniasis are considered neglected tropical diseases, mainly because it affects people from countries with low socioeconomic indicators. In Brazil, both cutaneous and visceral forms are found in all federation states, and the specie Leishmania amazonensis presents a high pathogenic potential for humans and other hosts. The standard treatment for leishmaniasis uses pentavalent antimonials, however, the occurrence of many side effects has led to the search for alternative therapies. Vanillosmopsis arborea Baker, or candeeiro, is an Asteraceae plant, found in the Araripe National Forest, Ceará State. It has great economic potential, due to the presence of the bioactive compound α-bisabolol, widely used in pharmaceutical industry. Studies have demonstrated that V. arborea essential oil have antimicrobial, anti-inflammatory, gastroprotective and in vitro leishmanicidal activity against L. amazonensis. Our study evaluated the in vivo leishmanicidal activity of V. arborea Baker essential oil in the treatment of murine cutaneous leishmaniasis. For this, BALB/c mice were infected with L. amazonensis amastigotes and treated with different concentrations of the essential oil and the reference drug. The results showed that the essential oil showed antileishmanial activity in a concentration of 5% and low toxicity, demonstrating the therapeutic potential of α-bisabolol.